2016
DOI: 10.1007/s12061-016-9188-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Identification of Trip Stops from Smartphone Data

Abstract: As part of a 3-year study on cycling infrastructure, a smartphone app was developed to passively collect location information from about 500 participants resulting in 96 million observations. By using WiFi and network location rather than the Global Positioning System (GPS) receiver in the smartphones, the app is able to collect frequent and good quality location data for long periods of time without limiting the use of the smartphones for other purposes. Tests of the data collected using the smartphone app co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In recent years, use of GPS to inform both travel surveys and health research has increased enormously [34][35][36][37]39,41,42]. GPS data has the potential to resolve the Unknown Geographic Context Problem by facilitating a detailed understanding of how people experience their local environment on a day-to-day basis [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, use of GPS to inform both travel surveys and health research has increased enormously [34][35][36][37]39,41,42]. GPS data has the potential to resolve the Unknown Geographic Context Problem by facilitating a detailed understanding of how people experience their local environment on a day-to-day basis [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by identifying time gaps of an appropriate length (for example where there was a gap of greater than x minutes between one GPS recording and the next). Although we were unable to find previous studies that have used time gaps to identify trips, studies that have identified stops within trips have typically used periods of two to five minutes [ 36 , 38 , 45 ]. However, Schuessler and Axhausen [ 49 ] noted that longer periods may be appropriate in the case of poor signal reception, and indeed we found a period of ten minutes to be more appropriate here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations